Conformational analysis of m4(2)C-m4(2)C-m6(2)A: a chemically modified 3'-acceptor end of tRNA, studied by NMR and CD methods. - Doornbos, J (1983)
A study on the conformation of the title compound, C-C-A, and on its constituent dinucleotides is presented. 1H-NMR spectra at 360 and 500 MHz were completely assigned by decoupling experiments. Computer simulation of the spectra yielded precise proton-proton and proton-phosphorus coupling constant values. The coupling constants are analyzed in terms of torsion angles and of N- and S-type sugar pucker. 31P-NMR spectra gave some information about P-O backbone torsion angles alpha and zeta. CD spectroscopy was used to obtain insight in the base-base interaction. The C(1) and C(2) unit in C-C-A show normal preference for N-type conformation of the sugar ring, whereas the A(3) residue appears rather biased towards the S-conformation. The zeta and alpha backbone torsion angles in the C-C phosphodiester linkage in C-C-A appear to assume normal g-, g- conformation, the zeta, alpha combination in the C-A linkage is proposed to have a g+, t conformation. In the C-C fragment in C-C-A a regular stack is indicated; it is suggested that the C-A part adopts an unusual antiparallel base stack.